THE PRIORITY DIRECTIONS AND TASKS OF MODERN MILITARY EDUCATION - Popkov, B. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The scientific article presents a theoretical-practical analysis of the pedagogical issue on the prior directions and objectives for the development of military education in Ukraine under the conditions of integrating the Armed Forces of Ukraine into the structure of both NATOmembers and partners and the ongoing conduct of the Operation of United Forces in the East of Ukraine. The system of military education is to promote the restoring of the staff and personnel potential of the Armed Forces of Ukraine, create and establish the necessary preconditions for a definite and qualitive staffing procedure, with personnel capable of professional performance of the set tasks under the conditions of both peace and war. For a professional, disciplined, equipped with modern military equipment and mobile Armed Forces staffed with personnel conscious of the high patriotic duties to be performed is one of the crucial elements for the stable and sustainable development of our state. One of the prior directions of modern development for military education is the responsibility and transparent feedback of the educational authorities and the military educational institutions to the state and society for the quality of training military specialists in terms of assuring their capabilities and readiness to effectively and efficiently perform the service related combat functions as an integral part of troops (forces) in accordance with their positions under the conditions of peace and war. Based upon the scientific-practical analysis of literature, personal scientific and military experience the prior directions and ways of development of military education have been determined, namely the rule of law, the appropriate meeting of the normative-legal basis of military education to both national and European standards as well as the peculiarities of development of the main elements of the security and defense sector of Ukraine in terms of their interoperability with the structure of NATO-member countries; the integration of military education into an overall educational system nation-wide; the integration of the military education of Ukraine with the European military-educational area under the preconditions of maintaining and developing the progressive achievements of national military educational system, a natural connection and link between the military education and the national and world history, culture and traditions; the accessibility and competitiveness in the process of obtaining military education. The perspectives of further scientific research are the following: implementing the set tasks and objectives in terms of developing modern military education due to the development of authentic methods and practical recommendations including the development of the military-political situation in Ukraine.